âFrom Teacher-Centered to Students-Centered to Collaborative Learningâ Illuminating My Teacher Knowledge through Narrative Inquiry - Triyoko, Hanung (State Institute of Islamic Studies Salatiga, 2010)
Teacher knowledge refers to the ways teachers know themselves and their professional work situations. This paper applies the narrative inquiry method to illuminate my own teacher knowledge. Through each vignette told in this paper, I will inquire into what I know and feel about English teaching-learning process and illuminate my teacher knowledge by referring to what education experts say regarding particular concepts of English teaching-learning. My students and I will have greater chance to share the values behind the students-centered classroom interaction, the Internet-based learning, or other kind of learning to follow in the future when âweâ, not only âIâ redefine education practices at schoolsÂ Keywords: Narrative Inquiry; Teacher Knowledge; Vignette